Structure features of the intracellular polysaccharide from Ganoderma lucidum and the irrelative immune-anticancer activities of GLPs. Issue 2 (October 2016) - Sui, Xiao-chen; Guo, Qing-bin; Xia, Yong-mei; Cui, Steve W.; Shen, Jie; Zhang, Jue; Ding, Zhong-yang
Abstract: Polysaccharides have been generally assumed to present their anticancer activity via immunomodulation. To verify this hypothesis, a relevance study on immunomodulation on typical macrophage cell RAW 246.7 and inhibition on model human carcinoma cell HepG2 was carried out with Ganoderma lucidum polysaccharides (GLPs) from different sources and lipopolysaccharide. Three GLPs with similar molecular weight range were prepared; structure features of the unknown intracellular GLP (GLP-In) was characterized with NMR and GC-MS. Inhibition on HepG2 cells with polysaccharides was measured using MTT assay, and immunomodulation on RAW 246.7 cells was tested on cell viability and NO release. The results indicate that anticancer- ability on HepG2 cells has no relevance with the stimulation strength on RAW264.7 cells. All assayed GLPs and lipopolysaccharide expressed dose-dependent and similar stimulation on RAW264.7 cell, but some of them even stimulated the cancer cells. GLP-In (1, 4-α-glucan backbone) has much stronger inhibition on HepG2 cells than the fruiting body GLP (GLP-Fr); while GLP-Fr ( β -glucan) possessed stronger immunomodulation effect. GLP-In presented a broad-spectrum inhibition on most assayed carcinoma cells dose-dependently. This study elucidated the irrelative immune-anticancer activities of GLPs; GLPs may not present anticancer activity only via immunomodulation. Graphical abstract: The irrelative immune-anticancer activities of polysaccharides from Ganoderma lucidum . Highlights: The immune and anticancer activity of G. lucidum polysaccharides are irrelative. The GLPs expressed similar dose-dependent stimulation on RAW264.7 cell viability. GLP-In presented broad-spectrum inhibition on carcinoma cells dose-dependently. The detailed structure features of intracellular GLP (GLP-In) was disclosed.